Orçamentação de aviários utilizando tecnologias computacionais - Ramallo, Priscila (2021)
The budgeting for the construction of new aviaries is carried out based on similar works or on the forecast of expenditures, with this the worked margin can become too high, making the project unfeasible, or too low, which generates flaws in the schedule and lack of resources. The tools in BIM (Building Information Modeling) are used by builders to facilitate and speed up the control of works. When used, in the planning phase, they provide a leaner work. Combining this technology with computational tools accessible to aviaries builders, a standard model of civil construction for aviaries was developed, meeting biosafety standards. The projected shed was dimensioned and the data transferred to a detailed budget spreadsheet, with the function of raising costs and acting as a description of the work. The spreadsheet, implemented, in this work, is an easy-to-use, efficient, practical tool that allows the user to have greater control over the stages, costs and planning.